831 Bouveret's Syndrome (A Gallstone Disease Causing Gastric Outlet Obstruction): A Case Series and Review of Literature. (12th October 2021) - Adnan, A; Ahmed, M; Sultana, A; Vitone, L
Abstract: Bouveret's syndrome refers to a gastric outlet obstruction due to the impaction of a large gallstone following retrograde migration via a bilio-duodenal fistula. Although no clear management guideline has been formulated, different treatment modalities have been described, including endoscopic stone removal using classical endoscopic devices, like snares and forceps; or fragmentation of stones with new devices, such as laser and extracorporeal shockwave lithotripsy (EWSL). We report a case series of Bouveret's syndrome with interesting radiological and endoscopic findings which have been successfully managed either via endoscopic measures such as stone extraction and/or duodenal stenting, or surgical intervention. The report is followed by a literature review including diagnostic and management options of this rare condition. All our patients were elderly with multiple comorbidities. Two patients presented with upper gastro-intestinal bleeding, while the other two presented with abdominal pain and bilious vomiting. The diagnosis was confirmed by computerised tomography (CT) scan and upper gastro-intestinal endoscopy. Endoscopic stone removal was successful in one case. In one patient, stone was fragmented but could not be removed completely, so he was managed via duodenal stent insertion. The other two patients required surgical intervention. One case was complicated by gallstone ileus which required laparotomy and extraction of stones from two sites, while the other required subtotal cholecystectomy, stone extraction and repair of duodenal fistula. The patients recovered well. The diagnosis of Bouveret's Syndrome is made after performing appropriate imaging studies. The first line management option is endoscopic treatment. If this fails, surgical intervention is recommended.